THE QUALITY OF DELIVERY SERVICE IMPACT ON THAILAND POST CUSTOMER SATISFACTION: THE STUDY CASE OF RAMINTRA STATION - พุทธรักษา รัตนะ; ทวีสุข พีรภาว์ (Journal of Business Administration The Association of Private Higher Education Institutions of Thailand, 2018)
The purpose of this study is to examine the quality of delivery services of Thailand Post Co., Ltd., which has an impact on customers’ satisfaction. The focused respondent for this study is customers, who used the service at Ramintra Station, at least one time within a month. 400 surveys were conducted and the descriptive analysis was used in order to provide percentage, average score, and standard deviation. In addition, the multiple regression analysis was employed to examine the relationship between a dependent variable and an independent variable. Most respondents used EMS service than other services. Descriptions of respondents are as follows: between 30 to 39 years old; hold a college degree; work as civil services; public enterprise personnel; has a monthly income more than 30,001 baht. Overall, customer satisfaction is beyond expected rate because of confidence in quality services, customer attentiveness, trust, and responsiveness to customers need. All of these factors have an influential impact on the customer satisfaction.